OPTIMALISASI ALOKASI SUMBERDAYA RUMAHTANGGA TANI MELALUI INTEGRASI USAHATANI TANAMAN DAN SAPI POTONG DI GUNUNGKIDUL YOGYAKARTA - Rini Widiati; Krishna Agung Santosa; Sri Widodo; Masyhuri Masyhuri (Agro Ekonomi, 2002)
The objective of this research is to assess the optimization of cattle farm household resources. The research was carried out by survey on samples of cattle farmers from two villages in Playen regency, Gunung Kidul district. The data collected were analyzed quantitatively using linear programming model and sensitivity analysis using BLPX 88 program. The model validation was carried out using confidence interval. The result of the research shows that most cattle farmers are poor in resources that they always combine their cattle farming activities with other activities specially crop activity to fulfill their daily need. This condition indicates that although the scale of cattle farm is small but it exist and continuous because there are mutual support and dependancy amoung activities. In general, the optimum resource allocation can increase their income over their family consumption.